Latihan Submaksimal dalam Hiperbarik-Hiperoksia dan Perubahan Fraksi Ejeksi pada Subjek Sehat - JOVIE, BENNY; PRATIKNYA, DJATIWIDODO EDI; KURNIAWAN, I MADE PRASETYA (Universitas Hang Tuah, 2025)
Coronary artery disease (CAD) is a leading cause of global morbidity and mortality. An important parameter in assessing left ventricular function is the ejection fraction (EF), which reflects the heart's ability to effectively pump blood into the systemic circulation. In recent decades, hyperbaric oxygen therapy (HBOT) has attracted attention as a non-pharmacological adjunct modality in the management of ischemic heart disease. The type of research is a true experimental research design with a randomized control group pretest - posttest with a sampling technique used is simple random sampling. The population in this study were 30 soldiers from the Surabaya Marine Corps Health Corps. In this experiment in both groups, the results obtained were p<0.05, which means that there is a difference in the pre and post results. When performing submaximal exercise in a hyperbaric-hyperoxic environment, cardiovascular adaptations occur, namely changes in afterload, preload, and myocardial oxygenation. Increased PaO₂ and dissolved oxygen can increase in stroke volume so that LVEF can appear to increase depending on the patient's baseline status. The conclusion of this study shows that submaximal exercise in hyperbaric-hyperoxy conditions provides better results and can even provide results that show normal results.